The Effect of Implementing Student Pictorial Worksheet on the Vocabulary Skill of Student Wangsaphung School, Thailand - Isnaini Farikha Ramadhani; Piyaporn Srimuang; Woravalan W; Ulfatul Ma’rifah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The social and behavioral changes in the field of education have occurred. The students have fallen far behind one and another especially in English education on mastery vocabulary. The researcher conducted in pre-experimental with a one group design pretest-posttest design with quantitative data used. This data uses respondents from 36 students in the Thai Wangshapung School. data in the study were collected using test instruments (pre-test & post-test) with analysis carried out including validity tests, reliability tests, normality tests, T-tests and descriptive data .So this research conduct to find out if there is a change in their vocabulary skills in their learning outcomes when using pictorial worksheets that assist with new technology canva. there is a significant difference in improving student learning outcomes on vocabulary skills. This is shown by the evidence of the t-test analysis value which is p value or Sig. (2-tailed) < .05 or .000 < .05. It means that H0was rejected and Hawas accepted; In other words, there was a significant difference between participants' pretest and post test scores. Which means There is an effect of the implementing student pictorial worksheet for vocabulary skill in learning outcomes. some academic researchers focus on examining the use of worksheets themselves without the use of images in order to attract students, and some of them have used image media but with the level of playground education (PRESCHOOL) or kindergarten. But the research needed is to improve students' English skills (vocabulary) with the help of pictorial worksheets as this researcher conducted research in this study.